Comparing short-, long-, and oblique-axis approaches to ultrasound-guided internal jugular venous catheterization: A meta-analysis of randomized controlled trials. Issue 3 (March 2019) - Chen, Jen-Yin; Wang, Li-Kai; Lin, Yao-Tsung; Lan, Kuo-Mao; Loh, El-Wui; Chen, Chih-Heng; Tam, Ka-Wai
Abstract : BACKGROUND: Internal jugular venous catheterization is performed for numerous therapeutic interventions. Although ultrasound-guided internal jugular venous catheterization is the gold standard for this procedure, complications can still occur. Various scanning axes, namely, the short axis (SA), long axis (LA), and oblique axis (OA), have been developed to ameliorate these complications. This study compared the efficacy and safety of SA, LA, and OA approaches. METHODS: PubMed, Embase, and Cochrane Library databases were searched for studies published before September 2018. Only randomized controlled trials were included. We conducted meta-analyses using a random-effects model. Treatment efficacy was measured by total success rate, first-pass success rate, number of needle passes, and incidence of complications, namely, arterial puncture, hematoma, and catheter-related bloodstream infection. RESULTS: Six randomized controlled trials with 621 patients were included. No significant differences were observed in total success rate and first-pass success rate, as well as in the arterial puncture, hematoma, or catheter-related bloodstream infection complications between SA and LA approaches. Moreover, no significant difference was found between SA and OA approaches in terms of total success rate, first-pass success rate, number of needle passes, and complications of arterial puncture and hematoma. However, the number of needle passes was significantly fewer in SA approach than in LA approach (weighted mean difference, −0.18; 95% confidence interval, −0.35 to −0.01). CONCLUSION: None of the scanning axes exhibited unique features that could enhance their suitability for application. Hence, scanning axes should be selected by considering various factors that include patient characteristics, clinician expertise, and ease of procedures. LEVEL OF EVIDENCE: Systematic review and meta-analysis, level I. Abstract : Supplemental digital content is available in the text.